Andrographolide Reduces Neuroinflammation and Oxidative Stress in Aged Octodon degus - Lindsay, Carolina B.; Zolezzi Moraga, Juan Manuel; Rivera, Daniela S.; Cisternas, Pedro; Bozinovic, Francisco; Inestrosa, Nibaldo C. (My University, 2020)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder in which superior brain functions, such as memory and cognition, are impaired. Currently, no effective treatment is available for AD. Although andrographolide (ANDRO), a compound extracted from the herb Andrographis paniculata, has shown interesting effects in models of several diseases, including AD, its effects on other molecular changes observed in AD, such as neuroinflammation and oxidative stress, have not yet been studied. To evaluate the impact of ANDRO-based intervention on the levels of amyloid-beta (A beta) and neuroinflammatory and oxidative stress markers in the brains of aged Octodon degus, a Chilean rodent, fifty-six-month-old O. degus were treated intraperitoneally with 2 or 4 mg/kg ANDRO. Vehicle-injected and 12-month-old O. degus were used as positive controls. Then, the protein levels of selected markers were assessed via immunohistochemistry and immunoblotting. ANDRO significantly reduced the total A beta burden as well as astrogliosis and interleukin-6 levels. Moreover, ANDRO significantly reduced the levels of 4-hydroxynonenal and N-tyrosine adducts, suggesting a relevant reduction in oxidative stress within aged O. degus brain. Considering that O. degus has been proposed as a potential "natural" model for sporadic AD due to the development of neuropathological markers that resemble this pathology, our results suggest that ANDRO should be further studied to establish its potential as a therapeutic drug for AD.
Keywords: andrographolide; amyloid-beta; neuroinflammation; oxidative stress; alzheimer's disease; octodon degus